Diffuse Optical Imaging: Safe and Functional Medical Imaging Technique - Omnia Hamdy; Mahmoud F. Hassan; Nahed H. Solouma (Journal of Public Health International, 2018)
Optical imaging method provides safe and encouraging tool in many medical applications. In this editorial, principle operation, instrumentation, medical applications and advantages of diffuse optical imaging technique are presented and discussed.
Keywords: Diffuse optical imaging